2014
DOI: 10.1016/j.ajpath.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Long Interspersed Element-1 Protein Expression Is a Hallmark of Many Human Cancers

Abstract: Cancers comprise a heterogeneous group of human diseases. Unifying characteristics include unchecked abilities of tumor cells to proliferate and spread anatomically, and the presence of clonal advantageous genetic changes. However, universal and highly specific tumor markers are unknown. Herein, we report widespread long interspersed element-1 (LINE-1) repeat expression in human cancers. We show that nearly half of all human cancers are immunoreactive for a LINE-1-encoded protein. LINE-1 protein expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
327
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 273 publications
(357 citation statements)
references
References 32 publications
29
327
0
1
Order By: Relevance
“…These cases are representative of one of the most lethal malignant diseases in women, and we have previously reported high levels of LINE-1-encoded protein expression in these malignancies (37). Using TIPseq and TIPseqHunter, we found a total of 36 somatically acquired, tumor-specific insertions in five of the eight individuals.…”
Section: Identification Of Tumor-specific Insertion Sites and Pcr Valmentioning
confidence: 97%
See 1 more Smart Citation
“…These cases are representative of one of the most lethal malignant diseases in women, and we have previously reported high levels of LINE-1-encoded protein expression in these malignancies (37). Using TIPseq and TIPseqHunter, we found a total of 36 somatically acquired, tumor-specific insertions in five of the eight individuals.…”
Section: Identification Of Tumor-specific Insertion Sites and Pcr Valmentioning
confidence: 97%
“…High proportions of both types of tumors aberrantly express LINE-1 encoded ORF1p protein (37), an RNA-binding protein critical for LINE-1 retrotransposition. Both have previously been shown to permit somatic retrotransposition events (22,25,27).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs and lncRNAs may regulate gene expression directly or indirectly through competing endogenous RNA (ceRNA) networks. 68 In normal somatic cells, L1 retrotransposition is suppressed 22,31 and L1 transcripts are degraded or processed into regulatory RNAs that maintain cell homeostasis, 19,21,24,66,67 whereas in cancer, one study found that L1 transcripts were potentially biased toward cDNA formation and retrotransposition, 69 leading to speculation that deregulated regulatory RNA networks may drive tumorigenesis.…”
Section: Functions Of L1s In Cancer Retrotransposition-dependent Funcmentioning
confidence: 99%
“…22,25 However, in line with L1 hypomethylation during tumorigenesis, [31][32][33][34] L1s can be reactivated and may participate in the pathological processes of cancer initiation and progression. 3,9,35 In 1988, Morse et al 36 reported a case of L1 insertion into c-myc gene in a breast cancer sample.…”
Section: Landscape Of L1 Retrotransposition In Cancermentioning
confidence: 99%
See 1 more Smart Citation